Il dipinto di Teodoro Matteini con Angelica e Medoro nella Glittica - Tassinari, Gabriella (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
The difficulty of representing the paintings in the gems has determined their lesser success in the glyptic repertoire compared to the representation of the sculptures. However, the engravers received a successful painting, such as the one painted by Teodoro Matteini in 1786: Angelica and Medoro carving their names on the bark of a tree, scene from the Orlando Furioso of Ariosto. This study analyzes the reproduction of the painting in the glyptic. The image appears on high quality intaglios and cameos by famous engravers, such as Giovanni Beltrami, Clemente Pestrini, Domenico Calabresi, who sometimes make variations to the composition; on anonymous gems, and in shell, cheaper material. A cameo mounted on the lid of a box / snuffbox in Ischia’s lava, a fashionable vehicle for the transmission of messages, testifies to the intense diffusion and circulation of Matteini’s painting.